AN ONLINE METHOD FOR THE DETERMINATION OF ORGANOCHLORINE PESTICIDE-RESIDUES IN SOYBEAN DERIVATIVE - Polese, L.; Minelli, E. V.; Ribeiro, M. L. (Soc Brasileira Quimica, 1994)
An on-line method for the determination of organochlorine pesticide residues in soybean bagasse is described. The extraction and cleanup steps are combined into one step by transferring the sample to a chromatographic column prepacked with alumina and silica gel. The pesticides are eluted with n-hexane (fraction 1) and n-hexane:dichloromethane 8:2 (fraction 2). The fractions are analyzed using gas liquid chromatography with electron capture detection. Mean recoveries of the 13 ''in vitro'' fortified pesticides at levels of 1.5-600 ppb ranged from 73 to 104%. Comparison of this method with other methods for fatty samples indicates that this is an improvement in accuracy, precision, for analysis time.
Keywords: ORGANOCHLORINE PESTICIDES; SOYBEAN BAGASSE